Special Forces Heroes: Extraordinary Stories of Daring and Valour - Ashcroft, Michael; Foreword by Mcnab, Andy (London Headline Review, 2008)
Tells the stories of forty heroes, all awarded bravery medals for their conduct during special forces missions over the last 150 years. Often covert hit-and-run operations involving very small numbers of highly skilled men, those who partake in these missions know that their goals involve a high level of risk.
Includes Colored Illustrations and Index.
Keywords: Special forces (Military science) -- Great Britain -- History -- 20th century